Liver Xenotransplantation in a Nonhuman Primate Model - Vagefi, Parsia A.; Navarro Álvarez, Nalu (My University, 2019)
Xenotransplantation using pigs is now considered a potential option to tackle the prevalent scarcity of liver grafts if the immunological and coagulation barriers can be overcome. Significant improvements have been made in overcoming graft loss due to hyperacute rejection with the development of genetically engineered α1,3-galactosyltransferase KO (GalT-KO) pigs. However, survival after liver xenotransplantation (LXT) has remained short, mainly due to the severe thrombocytopenia seen right after graft reperfusion, resulting in profound bleeding complications, intense graft thrombotic microangiopathy (TMA), and the subsequent graft loss. We have recently proven that thrombocytopenia and TMA can be overcome with exogenous administration of human coagulation factors, and thus, survival has improved. We here describe the technical procedure of our pig-to-baboon liver xenotransplantation model using exogenous coagulation factors and give detailed information on peri- and postoperative care of the transplanted animals.